(untitled) (Revista "Boletín el Conuco", 2020)
The document aims to show some of the new functions that SME managers in Colombia will have to face from the moment the decision was made to carry out the process of adoption and implementation of international financial reporting standards (IFRS). Some general aspects of these rules are presented, the different responsibilities of the actors, the paradigms change of the managers, the importance of the creation of the accounting policies, the decision making based on the presentation of new models and the importance for the interest groups. Through a description of experiences and policies related to the preparation and presentation of financial statements based on IFRS, and a secondary information analysis of the manager’s specific functions supported in a bibliographic review. The result of the investigation reflects the importance of the role that the manager must take on the new model of implementation and presentation of the financial statements.